Pelatihan Literasi Digital Untuk Mahasiswa di Era Pandemi COVID-19 - Tuwu, Darmin; Hos, Jamaluddin; Roslan, Suharty; Anggraini, Dewi; Masrul; Rusli, Muh. (Indonesian Journal of Community Services, 2022)
In the era of the Covid-19 pandemic, the world of education has entered the digital era, where the learning process no longer runs face-to-face in the classroom but has taken place on the internet network (online) that utilizes advances in information technology. Students are required to be able to keep up with technological developments so that they have basic knowledge about digital literacy which is used to operate various forms of online learning platform media such as Zoom, Zoom Meeting, Google Classroom, WhatsApp, and e-mail. The purpose of the training activity is to provide digital literacy skills to students so that they can access information technology-based information sources. The method of conducting the training is online using the Zoom Meeting, WhatsApp, and Gmail.com email applications. The results of the training activities show that after participating in digital literacy training activities, students' abilities can increase, especially in terms of utilizing the Zoom Meeting application, and searching for literature through Google Scholar, Mendeley.com, and other search engines. A high level of digital literacy can indirectly affect student learning outcomes. So good digital literacy skills are needed so that the use of information and communication technology in the implementation of online learning can run according to the specified goals. Digital literacy skills play an important role in supporting the success of online learning and the success of student studies.